Reflexiones en torno al posible conflicto correlacional entre la inteligencia artificial y el futuro de la sociedad humana - Sánchez Saca, Pamela Michelle (My University, 2019)
The notion of Artificial Intelligence refers to a particular type of technological intelligence that, although it has its starting point in the human person, can operate independently of it, in many ways surpassing the cognitive and procedural capabilities of humanity. The general objective of the essay is to provide reflections on the possible correlational conflict between artificial intelligence and the future of human society. In general, three possible conflicting scenarios are addressed, which were described as specific, scope and meaning of artificial intelligence; the advent of artificial intelligence in the 21st century; artificial intelligence and human society. Each of these scenarios is addressed in a particular section in order to describe its correlational state between the agents of artificial intelligence and the social. Through a qualitative methodology of review and documentary analysis, the same that allowed to examine and describe the object of study by performing an analysis of qualities, causes and factors. Therefore, we reviewed various texts of a technological nature that contributed to the foundation of the state of art, it is concluded that humanity has defined itself as the preponderant and hegemonic species of the planet, by reason of its rational potential that It has allowed transforming its environment to serve its particular interests. Of having to live with other forms of equal or superior intelligences in the use of critical or instrumental reason, it would also have to rethink ontologically its existence and its protagonist position in history.
La noción de Inteligencia Artificial refiere a un tipo particular de inteligencia tecnológica que, aunque tiene su punto de inicio en la persona humana, puede funcionar con independencia frente a la misma, llegando a superar en muchos aspectos las capacidades cognitivas y procedimentales de la humanidad. El objetivo general del ensayo es aportar reflexiones en torno al posible conflicto correlacional entre la inteligencia artificial y el futuro de la sociedad humana. Se abordan tres posibles escenarios lo cuales fueron descritos como específicos, alcances y significados de la inteligencia artificial; el advenimiento de la inteligencia artificial en el siglo XXI; inteligencia artificial y sociedad humana. Cada uno de estos escenarios se aborda en una sección particular para poder describir su estado correlacional entre los agentes de la inteligencia artificial y lo social. Mediante una metodología cualitativa de revisión y análisis documental, permitió examinar y describir el objeto de estudio realizando un análisis de cualidades, causas y factores. Por consiguiente, se revisó diversos textos de naturaleza tecnológica que contribuyeron a la fundamentación del estado del arte, se concluye que, la humanidad se ha definido a sí misma como la especie preponderante y hegemónica del planeta, en razón, de su potencial racional que le ha permitido transformar su entorno al servicio de sus intereses particulares. De tener que convivir con otras formas de inteligencias iguales o superiores en el uso de la razón crítica o instrumental, además tendría que replantearse ontológicamente su existencia y su posición protagónica en la historia.
Keywords: CONFLICTO; SOCIEDAD HUMANA; FUTURO; INTELIGENCIA ARTIFICIAL